The Influence of Environmental Social Governance, Green Investment, and Profitability on Firm Value: Study on the SRI-KEHATI Index (2019-2023) - Hasanah , Nurlaila Luthfiyah; Paramita, Veronika Santi (Sinergi International Journal of Economics, 2025)
The purpose of this study is to analyse the factors that affect the value of companies in the SRI-KEHATI index for the 2019-2023 period. Researchers suspect that ESG, GI, and Profitability factors affect the firm's value. The leading indicator used to assess how a firm is performing and valued by investors is the stock price. Stock prices on the SRI-KEHATI index fluctuated from 2019-2023. From 2022 to 2023, the stock price of the SRI-KEHATI index tended to increase in line with public awareness of the environment, but the firm's value in both years decreased. The development of eco-friendly industries has now become a global trend, so companies that have implemented ESG and GI principles are believed to be able to grow and attract the interest of many investors. The quantitative method with descriptive analysis of causality is the method used in this study; the data source is secondary, and the type of data is the panel. The researcher used the purposive sampling technique to determine 15 companies selected as a sample. Researchers analyse the data using quantitative analysis. The findings of the study show that ESG has a negative impact on firm value, GI does not affect firm value, and firm value is positively affected by ROE. Meanwhile, ESG, GI, and ROE simultaneously affect a firm's value.